Sustenance of Tax Administration by Information and Communications Technology in Nigeria - Oseni, Michael (Archives of Business Research, 2016)
The focus of this paper rests on the nexus of information and communications technology in administration of tax in Nigeria. Nearly every sector of the national life has been affected by the ICT.  ICT has defined the business, social and personal environment of the country. The study used content analysis method to highlight challenges that are peculiar to tax administration in Nigeria. The periods where the rule of the thumbs were used in determining the assessable income of tax payers compared to the recent times where ICT are used in tax administration to near pinpoint accuracy were analysed. With the use of ICT, leakages were reduced. It was found out that there is no hiding place for tax evaders with the use of this modern technology since the all potential taxpayers are captured by the system. Nevertheless the use of ICT can be catastrophic if carelessly employed by both the tax payers and the tax administrators as scammers and hackers of the internet facilities can utilize the ignorance or the lax security of the system.